Modelling the role of predation on disease burdens of prey. Issue 7 (4th July 2022) - Gagne, Roderick B.
Abstract: Research Highlight: Brandell, E. E., Cross, P. C., Smith, D. W., Rogers, W., Galloway, N. L., MacNulty, D. R., Stahler, D. R., Treanor, J. & Hudson, P. J. (2022). Examination of the interaction between age‐specific predation and chronic disease in the Greater Yellowstone Ecosystem. Journal of Animal Ecology, 00, 1–12. https://doi.org/10.1111/1365‐2656.13661 . Predation can alter disease dynamics in prey. If predators select for infected individuals, they can reduce disease burdens. In other cases, predators can increase disease burdens via various mechanisms such as altered prey behaviour. The influence of predation on disease dynamics is a result of interactions among various traits of the predators, prey and the pathogen itself. For example, pathogens tend to vary with age and predators typically select for certain age classes. Thus, the overlap between ages selected by predators and those infected will likely contribute to any effects of predation on reducing disease burdens. In this paper, Brandell et al. (2022) develop a model to evaluate the predator cleansing effect given age‐based variation in pathogens and predation. The model was developed for Chronic Wasting Disease (CWD) infections in deer and elk facing predation by cougars and grey wolves in the Greater Yellowstone Ecosystem. The results indicate that predators can reduce CWD outbreak size, especially if selecting for infected individuals. CWD is an always fatal disease and this work suggests that predators could reduce disease burdens in cervids. The model is also applicable to other systems and promises to further our understanding of the role of predation on disease in prey, as well as drive future empirical studies. Abstract : This research highlight showcases the work of Brandell et al., Examination of the interaction between age‐specific predation and chronic disease in the Greater Yellowstone Ecosystem https://doi.org/10.1111/1365‐2656.13661 .